2016
DOI: 10.1186/s12879-016-1840-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with clinical outcome in 25 patients with avian influenza A (H7N9) infection in Guangzhou, China

Abstract: BackgroundGuangzhou reported its first laboratory-confirmed case of influenza A (H7N9) on January 10, 2014. A total of 25 cases were reported from the first wave of the epidemic until April 8, 2014. The fatality rate was much higher than in previous reports. The objective of the current work was to describe the clinical and epidemiological characteristics of A (H7N9) patients in Guangzhou and explore possible reasons for the high fatality rate.MethodsClinical and epidemiological information regarding A (H7N9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
6
24
0
3
Order By: Relevance
“…The clinical manifestations were in consistence with the previous data of 41, 99, and 138 patients analysis in Hubei province [46,48,50]. Fever and cough were the dominant symptoms whereas upper respiratory symptoms and gastrointestinal symptoms were rare, suggesting the differences in viral tropism as compared with SARS-CoV [51], MERS-CoV [52], and influenza [53]. The elderly and those with underlying disorders (i.e., hypertension, chronic obstructive pulmonary disease, diabetes, cardiovascular disease), developed rapidly into acute respiratory distress syndrome, septic shock, metabolic acidosis hard to correct and coagulation dysfunction, even leading to the death [48] (lower panel, Fig.…”
Section: Clinical Symptomssupporting
confidence: 85%
“…The clinical manifestations were in consistence with the previous data of 41, 99, and 138 patients analysis in Hubei province [46,48,50]. Fever and cough were the dominant symptoms whereas upper respiratory symptoms and gastrointestinal symptoms were rare, suggesting the differences in viral tropism as compared with SARS-CoV [51], MERS-CoV [52], and influenza [53]. The elderly and those with underlying disorders (i.e., hypertension, chronic obstructive pulmonary disease, diabetes, cardiovascular disease), developed rapidly into acute respiratory distress syndrome, septic shock, metabolic acidosis hard to correct and coagulation dysfunction, even leading to the death [48] (lower panel, Fig.…”
Section: Clinical Symptomssupporting
confidence: 85%
“…We also conducted a subgroup meta-analysis on UMCs associated with fatalities of H7N9-infected cases by adjusting for the effects of age and gender. As shown in Figure 2 , we found that age (60 years or older; AOR: 1.86; 95% CI: 1.05–3.29, z =2.14; P =0.032) 6 , 13 , 15 – 17 , 19 , 21 and gender [male: AOR: 1.68 (95% CI: 1.16–2.45), z =2.73, P =0.006; female: AOR: 1.88 (95% CI: 1.03–3.59), z =1.99, P =0.044] 5 , 13 , 15 – 17 , 19 , 21 were significantly associated with death in H7N9 patients with UMCs compared to H7N9 patients without any UMCs. However, differences in 0–59 years aged subgroup were not significantly associated with changes in the risk of death regardless of UMCs ( P >0.05, I 2 <50.0%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 68%
“…We designed a subgroup meta-analysis to explore the association between UMC types and death in H7N9 patients. In this subgroup analysis, in which we analyzed the presence or absence of certain UMC types, we found that having two or more UMCs (OR: 2.24; 95% CI: 1.02–4.92, z =2.01; P =0.044), 12 14 , 17 CRD (OR: 1.81; 95% CI: 1.05–3.11, z =2.15; P =0.032), 4 , 5 , 7 , 12 , 14 , 19 , 21 and CCD (OR: 1.63; 95% CI: 1.11–2.38, z =2.49; P =0.013) 4 7 , 13 , 14 , 19 , 21 had a statistically significant association with death. No associations were found for other UMC types ( P >0.05) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…One example of these events is the avian-origin H7N9 influenza virus outbreak currently undergoing in China (Hai et al, 2013). While mild illnesses in human H7N9 cases have been observed, many patients have developed severe respiratory illness (Wang et al, 2016). The virus appears not to be transmitted from person to person, although limited non sustained human-to-human transmission has been observed within some families (Liu et al, 2013).…”
mentioning
confidence: 99%